Pengaruh Penerapan Sistem Akuntansi Keuangan, Pengendalian Internal dan Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Klungkung) - Utami, Ni Putu Sri; Merta , I Wayan Gede; Manuaba, I. B Made Putra (Jurnal Riset Akuntansi Warmadewa, 2020)
Accounting has a vital aspect in the corporation, because accounting is the language of business. Accounting produces information that describes the corporate financial performance in a particular period as well as the corporate financial conditions on a certain date. What is said to understand about accounting is a misunderstanding as well as shrewdness in how the accounting process is carried out until it becomes a financial report by referring to the principles and standards for the preparation of the governmental financial statements that are applied in regulation No.71 of 2010 concerning Government Accounting Standards. Based on the description above, the objectives of the research are: The Effect of the Implementation of the Financial Accounting System, Internal Control and Accounting Understanding on the uality of Local Government Financial Statements. The research was conducted at the Financial Management Agency and Regional Income of Klungkung Regency with a total sample of 55 people. Data were collected using the uestionnaire method and documentation study. Data analysis techni ues with PLS analysis. The results showed that the Financial Accounting System, Internal Control and Accounting Understanding positively had a significant effect on the uality of Regional Government Financial Statements at the Head of the Financial Management Agency and Regional Revenue of Klungkung Regency.